(untitled) (Fiep Bulletin - online, 2011)
The study aimed to investigate the nutritional status of children 07 to 10 years of primary education in public and urban area of Macapá (AP). The sample consisted of 2071 elementary school students of both sexes, enrolled, selected by proportional random sampling by schools and conglomerate class. As a tool for checking the weight of school children used a digital scale with a capacity of 150 kg and a stadiometer tape type, with 2000 cm with an accuracy of 01 mm. Anthropometric evaluation was done by weight, height and age. Nutritional status was assessed by the criterion of WATERLOW (1976), the benchmark was the NCHS. Inferential comparison between groups was performed using the chi-square (x2). With the level of significance of the null hypothesis of 5% (p <0.05). The result of the assessment of nutritional status between the ages obtained p-value <0.001 * which is highly significant indicating real differences, as it turns out that the ages of 7 to 8 years category predominates Eutrophic (46.7%), at the age of 9 years, the predominant category Obese (32.2%). At the age of 10 years had a greater proportion of categories malnutrition (33.3%) and obesity (30%). The status, it was observed that the highest rates of malnutrition appeared in the North of the males, and in the southern region of females, and the malnutrition appeared high in both regions. Conclusion: Malnutrition was found in regions of Macapá can be considered a public health problem of great relevance to society.